Design of real-time transmission system for underwater panoramic camera based on RTSP - Wenhui Wang; Yongqi Li; Rufei He (PLoS ONE, 2025)
The underwater environment is complex and variable, with limited transmission bandwidth and strong clutter and interference signals, which make the collected images susceptible to adverse effects such as attenuation and diffusion, resulting in image signal transmission congestion. In the current transmission system application process, the interference noise present in the collected original image will increase the average reprojection error of the image; And some systems have complex data collection processes, requiring the deployment of multiple sensors, which increases data transmission time. In order to improve the ability and efficiency of underwater data collection and transmission, and ensure the quality of underwater multimedia data transmission, a real-time transmission system for underwater panoramic cameras based on RTSP (Real Time Streaming Protocol) was designed. In the data acquisition layer, after setting the relevant parameters of the underwater panoramic camera through camera calibration method, the calibrated underwater panoramic camera is used to collect underwater data. The collected underwater data is compressed and encoded by the encoder in the data encoding layer, and then transmitted to the RTSP server layer. After receiving compressed and encoded underwater data, the RTSP server layer stores it on disk and encapsulates it into RTP (Real-time Transport Protocol) packets. The congestion control method using RTCP feedback monitors the network status in real-time and dynamically adjusts the data transmission rate, effectively avoiding the occurrence of network congestion problems. The RTSP application layer client receives data from the RTSP server, implements restructuring analysis through RTP packets, and sends the restructured frame data into a double buffer waiting for decoding and playback or file recording, achieving real-time transmission of underwater panoramic cameras. The experimental results show that the data transmission effect and quality of the system are good, and the average reprojection error of the calibrated image is 0.12 pixels; During the process of data collection and transmission, the effective time window of the eye diagram is the largest, and the waveform of the top-level data transmission tends to be stable with the smallest fluctuation amsplitude; Dynamically adjust the data transmission rate, control the network packet loss rate below 0.5%, and improve the real-time transmission efficiency of underwater data.